Study on the structural transition and thermal properties of Ni3Nb-D022 phase: First-principles calculation. (5th February 2018) - Lin, Y.C.; Jiang, Xing-You; Luo, Shun-Cun; He, Dao-Guang
Abstract: The structural transition and thermal properties (thermodynamic and thermoelastic properties) of Ni3 Nb-D022 phase are investigated by first-principles combined with quasi-harmonic approximation method. The computed results show that the structural transition from Ni3 Nb-D022 to Ni3 Nb-D0a primitively occurs at the temperature range of 950–960 K. The phase structure is thermally stable but easily compressed. The heat capacity tends to Dulong-Petit limit when the temperature is higher than 900 K. The computed thermoelastic properties of Ni3 Nb-D022 phase reveal the slight softening trends with the increased temperature, indicating that the Ni3 Nb-D022 phase is well heat-resistance. Additionally, Ni3 Nb-D022 phase is ductile at the temperature range of 0–900 K, and its hardness decreases with the increased temperature. Moreover, the Ni3 Nb-D022 phase is anisotropic and has a distinct dependence on crystal orientations. The strengths of chemical bond along [100] and [010] orientations on (001) plane are slightly weakened with the increase of temperature. Graphical abstract: Highlights: Structural transition and thermal properties of Ni3 Nb-D022 phase are studied by first-principles calculation. Structural transition from Ni3 Nb-D022 to Ni3 Nb-D0a occurs at the temperature range of 950–960 K. Heat capacity tends to Dulong-Petit limit when the temperature is higher than 900 K. Ni3 Nb-D022 phase is anisotropic and has a distinct dependence on crystal orientations.